Perancangan dan Pemodelan Turbin Darrieus untuk Pembangkit Listrik Tenaga Arus Laut (PLTAL) - Prayoga, Wahyu Adi; Permatasari, Rosyida (MESIN, 2019)
Sea current energy is one of the new and renewable energy that is currently being developed to replace fossil energy which is starting to deplate its availability. Sea current energy research continues to be developed. One of the studies that can be developed is modeling laboratory-scale sea currents, so that it is necessary to design a model of Sea Current Power Plants that aims to improve the process of understanding the energy. In this design, a model of Sea Current Power Plant with a capacity of 150 Watt is designed using the Darrieus Turbine. The design results some data such as : diameter of 428 mm for turbine rotor, height of 327 mm for turbine rotor, chord length of 0.04 m for 3 NACA 0018 airfoil blades, and a transmission ratio of 1 : 5 for transmission systems using a straight gear gearbox. In addition, the turbine generated 205.5 rpm rotation at  flow rate of 1.15 m/s with turbine efficiency of 40%.